Analysis of the Impact of Fatherlessness on Early Childhood Character Building in Gampong Tanjung Deah - Irhamna; Faridy, Faizatul (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
This study aims to analyze the impact of the absence of a father figure (fatherless) on the character development of early childhood in Gampong Tanjung Deah. Given the role of the father as an important figure in the psychosocial development of a child, his absence can significantly influence the formation of the child's character, particularly in the context of moral, ethical, and social values. This research employs a qualitative approach with a case study method to deeply explore the experiences, perceptions, and impacts of the absence of a father on young children in this community. Data were collected through in-depth interviews with mothers, caregivers, early childhood educators, as well as direct observations of children experiencing fatherlessness. The data were analyzed thematically to identify behavioral patterns and the effects resulting from the absence of a father. The findings of this study indicate that children growing up without a father figure tend to struggle with internalizing values such as discipline, responsibility, and self-control. Additionally, the absence of a father also affects children's self-esteem and their ability to engage in social interactions. This study recommends the importance of social support and the active role of mothers and the community in assisting the character development of children experiencing fatherlessness, to ensure the development of healthy and positive character traits. Penelitian ini bertujuan untuk menganalisis dampak fatherless terhadap pembentukan karakter anak usia dini di Gampong Tanjung Deah. Mengingat peran ayah sebagai salah satu figur penting dalam perkembangan psikososial anak, ketidakhadirannya dapat memberikan pengaruh signifikan terhadap pembentukan karakter anak, khususnya dalam konteks nilai-nilai moral, etika, dan sosial. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus untuk menggali secara mendalam pengalaman, persepsi, dan dampak dari ketidakhadiran ayah terhadap anak-anak usia dini di komunitas ini. Data dikumpulkan melalui wawancara mendalam dengan ibu, serta observasi langsung pada anak-anak yang mengalami kondisi fatherless. Analisis data dilakukan secara tematik untuk mengidentifikasi pola-pola perilaku dan dampak yang muncul dari ketidakhadiran ayah. Hasil penelitian ini menunjukkan bahwa anak-anak yang tumbuh tanpa figur ayah cenderung mengalami kesulitan dalam menginternalisasi nilai-nilai disiplin, tanggung jawab, dan pengendalian diri. Selain itu, ketidakhadiran ayah juga berdampak pada rendahnya rasa percaya diri dan kemampuan anak dalam berinteraksi sosial. Penelitian ini merekomendasikan pentingnya dukungan sosial dan peran aktif ibu serta komunitas dalam membantu pembentukan karakter anak-anak yang mengalami kondisi fatherless, guna memastikan perkembangan karakter yang sehat dan positif.